2009
DOI: 10.1093/eurjhf/hfp038
|View full text |Cite
|
Sign up to set email alerts
|

Self‐rated health and mortality in patients with chronic heart failure

Abstract: AimsIn patients with chronic heart failure (CHF), there is limited information on self-rated health (SRH). We aimed to examine the distribution of SRH and whether SRH is associated with mortality in patients with stable CHF. Methods and resultsWe enrolled 100 patients (71 + 11 years, 54% men, left ventricular ejection fraction 47 + 11%) in a prospective study with 48 months of follow-up. Self-rated health was assessed using a seven-grade descriptive scale: very good, good, quite good, average, quite poor, poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 39 publications
3
49
0
Order By: Relevance
“…Our findings on SRH distribution in patients with COPD confirm previous studies on such a relationship in patients with other chronic conditions (diabetes, cancer, chronic heart failure, chronic kidney disease) [8][9][10][11][12]. Our study also demonstrates that SRH is worse in patients with COPD than in healthy control persons and confirms previous COPD reports on the deterioration of SRH with advanced stages of disease.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings on SRH distribution in patients with COPD confirm previous studies on such a relationship in patients with other chronic conditions (diabetes, cancer, chronic heart failure, chronic kidney disease) [8][9][10][11][12]. Our study also demonstrates that SRH is worse in patients with COPD than in healthy control persons and confirms previous COPD reports on the deterioration of SRH with advanced stages of disease.…”
Section: Discussionsupporting
confidence: 91%
“…Clinicians could use SRH to identify those patients who might benefit from specific interventions, such as disease or case management [23]. Studies in other chronic diseases [8][9][10][11][12] have identified SRH as an independent predictor of mortality. Although such data in COPD are lacking, more attention in the clinical setting should be given to patients with COPD who rate their health unfavorably.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These simple questions can help identify patients who are a higher risk of future morbidity and mortality. 17,18,55 The inverse relationship between perceived health and the extent of general symptoms and diseases is plausible and supported by the literature. 17,18,56,57 However, the cross-sectional nature of this study limited our ability to test the causal associations.…”
Section: Discussionmentioning
confidence: 61%
“…As a single‐item question, SRH is known to be a multifaceted and powerful tool that can indicate a decline in physical functionality9 and predict mortality and morbidity in subjects with chronic disease10 and the elderly 11. SRH also has disease‐specific predictive capabilities and has been reported to be an excellent predictor of recurrent ischaemic events after myocardial infarction12 and of the exacerbation of chronic obstructive pulmonary disease 13.…”
Section: Introductionmentioning
confidence: 99%